Autologous Blood Injection for Treatment of Tennis Elbow - Karimi Mobarakeh, Mahmood (Kowsar, 2013)
BACKGROUND: Tennis elbow (TE) is a common myotendinosis. It was first described by Runge in 1873; different modes of treatment are used in management of TE. OBJECTIVES: This study aimed to report the results of autologous blood injection (ABI) in the treatment of TE. MATERIALS AND METHODS: A prospective case study was performed to evaluate the results of ABI in the management of TE. The level of pain based on Nirschl phase scale (NPS) and a visual analogue scale (VAS) was calculated before and 1, 3 and 6 months after injection; then satisfaction was assessed. RESULTS: Twenty-nine patients with diagnosed TE were treated by ABI (24% males, 76 % female). The mean age of the patients was 44.1 ± 5.2 years. The level of pain on VAS decreased from 6.46 ± 2.08 to 0.54 ± 0.7 (P=0.001) and on NPS from 6.15 ± 1.48 to 0.54 ± 0.76 (P = 0.001) 6 months after treatment. At the end of the study, 84% of patients expressed a high level of satisfaction. CONCLUSIONS: Given the acceptable outcomes, autologous blood injection can be considered a good treatment option for TE when traditional treatment has fails.